Mouse sn-glycerol-3-phosphate dehydrogenase: molecular cloning and genetic mapping of a cDNA sequence. - Kozak, L P (1983)
The isozymes of glycerol-3-phosphate dehydrogenase (GPDH; sn-glycerol-3-phosphate:NAD+2-oxidoreductase, EC 1.1.1.8) in tissues of the mouse are coded for by two structural genes, Gdc-1 and Gdc-2, located on chromosomes 15 and 9, respectively. In order to investigate the expression of these genes, we isolated a GPDH cDNA clone from a mRNA preparation isolated from brown adipose tissue. The GPDH cDNA clone was identified by colony hybridization and hybrid selection of a mRNA that was translated in vitro to produce immunoprecipitable GPDH protein. In blot analysis, the GPDH cDNA hybridized to a single mRNA species that migrated at the position of 23S ribosomal RNA. This GPDH cDNA clone was mapped to the Gdc-1 locus by identification of a restriction enzyme polymorphism present in genomic DNA isolated from Gdc-1 congeneic lines of mice.